ANALYSIS ON SUPPORT PROGRAM WITH CONVERSION FROM VACANT HOUSES INTO COMMUNITY BASES: A CASE IN SETAGAYA WARD, TOKYO - Shota Yamada,; Tatsuo Akashi, (PEOPLE: International Journal of Social Sciences, 2024)
The municipal government of Setagaya Ward established a consultation program for individual owners of vacant houses in July 2013 to convert them into useful places for the community. This service aims to match with owners of vacant houses and citizen groups such as non-profit organizations and has established 22 bases for the community in 10 years. The authors found that the majority of them are used for social welfare offering places for children, disabilities, or the elderly. These facts indicate the necessity of the role of the public sector’s program rather than private companies to promote the re-utilization of vacant houses into places of inclusionary use for the community.